Influência da formação de agregados e de nanopartículas de ouro nas propriedades microscópicas de corante rodamina 6G - Silva, Uéslen Rocha (2010)
The aggregate effect in rhodamine dyes is a subject widely exploited in previous literatures. The majority of the references investigated this effect through the heat generation or simply analyzing the absorption spectra. A few works used the dependence of the fluorescence quantum efficiency (n) with the dye concentration. However, none of them considered a general model for analyses of the experimental data. For instance, it was considered absorptions of both species (monomers and dimers), but not energy transfer (ET) and vice-versa; in general the dimers are taken as no-fluorescent; etc. Indeed, from both theoretical and practical viewpoints, n is one of the most important parameter of luminescent materials. In this dissertation, we investigated the effects of the aggregated formation of aqueous solutions of Rhodamine 6G (R-6G) on the thermal and optical properties, such as thermal diffusivity, dn/dT, n, and ET. From more complete analyses, i.e., taking into account absorptions of both monomers and dimers, that both are fluorescent, ET, etc, we explain very well the obtained results. The value achieved for nd of the dimers is relatively large and cannot be neglected in obtaining nm of the monomers. Using the Föster theory for dipole-dipole electric ET, we have concluded that ET between monomers-monomers and monomersdimers are very efficient and must be considered in this system. Preliminary results of Au nanoparticles (NPs) effects on the thermo-optical properties of R-6G are also presented, mainly on the aggregated formation and n. The behavior obtained for ofaqueous solutions of R-6G with Au NPs indicates that we must consider the presence of Au NPs on the nm determination